PENGGUNAAN AGREGAT SUB STANDAR DAN AGREGAT LOKAL UNTUK CAMPURAN BERASPAL - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
The study using sub standard aggregate and local agregate for asphalt mixed, it covers mixed design asphalt using five aggregates, there are : standard aggregate, sub standard aggregate that not fulfill the specification, marble aggregate, slag aggregate and limestone aggregate. The result of the mixed asphalt there are, limestone aggregate had a Marshall stability more higher than a standard mixed, is 1820 kg, when slag aggregate nave dynamic stability more higher than standard, is 2100 passing/minute, and permanent deformation also lower than a standard. The test of modulusresulient between slag and standard aggreate are similar, have a same number, but limestoe aggregate have a lower modulus on 25oC, is 41% lower than a standard mixed. The aggregate that have a bad performance is marble aggregate, that have a low Marshall stability is 16,7%, deformation permanent increase 18% and dynamic stability is lowe 52% than standard mixed, when the sub standard aggregate have a lower retain Marshall stability < 75% to original stability. To prove this result, it should be make an application on field, to know the similar performance on laboratory.